Development of Staphylococcus aureus-derived skin cancer therapeutics - Ong, Zi Xin (Nanyang Technological University, 2022)
The concept of using bacteria and bacterial products in cancer therapy has been around since the 19th century. As molecular targeted therapy increases in prominence, the search for novel cancer cell-specific therapeutic agents with low off-target effect continues. Staphylococcus aureus SA29213 was discovered to produce a protein toxin with specific toxicity towards cutaneous squamous cell carcinoma (SCC) cell line SCC-12. The protein toxin possesses a previously uncharacterised cell line-specific toxic effect towards cancerous keratinocytes at low concentrations while exerting minimal effects towards non-cancerous keratinocytes HaCaT. The toxin is proteinaceous, heat liable, and is enriched upon biofilm accumulation. Prolonged culturing of biofilm shifts the SA29213 secretome from possessing broad-spectrum toxicity to SCC-12-specific toxicity. Toxin-induced SCC-12 cell death is characterised with giant membrane bleb formation, DNA damage, and caspase-dependency. A multi-pronged omics approach was employed to identify the protein toxin responsible for the observed SCC-12-specific toxicity. First, genes involved in the regulation, production, and secretion of the toxin were identified with the screening of a novel SA29213 transposon mutant library for loss of SCC-12-specific toxicity. Next, a comprehensive in silico genomic study was conducted to associate genomic features to SCC-12-specific toxicity. Finally, the proteins associated with SCC-12-specific toxicity were identified through fast protein liquid chromatography (FPLC) protein fractionation and liquid chromatography tandem mass spectrometry (LC-MS/MS). These combined highlighted a candidate protein toxin which would be verified for SCC-12-specific toxicity in further studies. In this thesis, the generation of a novel SA29213 transposon mutant library is described. The library serves as an important S. aureus genetic tool and would be beneficial for the study of S. aureus-associated skin diseases. This thesis also describes novel methodology for the generation of S. aureus biofilm-conditioned media (BCM) in both a large volume and high-throughput configuration for the study of S. aureus secreted products. The development of the SA29213 SCC-12-specific protein toxin as a SCC therapeutic could potentially provide a non- or minimally invasive treatment alternative with minimal off-target effects on neighbouring non-cancerous cells. This would provide an alternative to, or complement, the use of surgical excision in the treatment of high-risk SCC.